Bioactive natural compounds as potential medications for osteogenic effects in a molecular docking approach - Yuqiong Wu; Yuqiong Wu; Yulan Liu; Yulan Liu; Yuanjin Xu; Yuanjin Xu; Ao Zheng; Ao Zheng; Jiahui Du; Jiahui Du; Lingyan Cao; Junfeng Shi; et al. (Frontiers Media S.A., 2022)
Bone defect repair and fracture healing are critical challenges in clinical treatments. Bioactive natural compounds are potential resources for medications for osteogenic effects. We have identified icariin, the effective ingredient of Epimedium pubescens, to promote osteogenic differentiation of bone mesenchymal stem cells (BMSCs) and repair bone defects. To explore more natural compounds with the potential modality for bone repair, in the present study, we employed an icariin-induced gene expression pattern as an osteogenic model and screened the Connectivity Map database for small molecules with gene expression signatures similar to this model. We verified the effectiveness of this molecule docking approach by introducing hydroxycholesterol, the second highest score of the similarity to icariin, into the osteoinductive experiments in vitro and demonstrated its excellent osteogenic effect on BMSCs compared with a BMP-2-positive control group. Based on the compatible result of hydroxycholesterol, subsequently, ginsenoside Rb1 was chosen as the most drug-like natural compound among the molecule docking results from icariin. Finally, ginsenoside Rb1 was demonstrated to promote the expression of osteoblastic genes and ALP activity in vitro and repair the calvarial defect of rats in vivo. The study aimed to provide diverse choices for clinical application in bone repair and functional regeneration.